Everyday Urban Neighbourhood Participation in Advanced Age - Conaglen, Jo (Auckland University of Technology, 2019)
Designing public polices and urban neighbourhoods that address ageing issues require a deep understanding of neighbourhood participation from the perspective of lived experience. The aim of this study was to understand the meaning of neighbourhood participation as experienced by adults over the age of 85 years. Interpretive phenomenological research method, informed by the writings of Hans-Georg Gadamer and Martin Heidegger, was used to study the phenomenon of everyday urban neighbourhood participation by adults in advanced age. There is much research and knowledge about the phenomenon written by people who are not yet in advanced age. This study was concerned with hearing what it is older adults had to say about everyday neighbourhood participation. Fifteen participants, nine women and six men, aged 86-96 years, were recruited from within the Auckland inner city boundary of the Waitemata District. All lived in their own home, participated in their neighbourhood, and were able to recall recent life situations. The participants were recruited via advertisements placed in community newspapers and on notice boards in places frequented by older adults, and through a third party associated with aged persons’ organisations. Interviews were audiotaped, transcribed, and worked into discrete stories of everyday experiences of neighbourhood participation. The participant-validated stories formed the data and, in dwelling with the data, three themes emerged as findings from this study. These interpretive findings of the everyday experiences were of ‘holding on to the everyday’ as participating, the experiences of ‘being neighbourly’ with relationships at the heart of participation, and the difficulties of ‘keeping-going’ as concern for holding on to abilities for participating in advanced age. Reflecting on the findings, participating in the ordinary everyday life of neighbourhood in advanced age both conceals and reveals the phenomenon of neighbourhood participation. My thesis is that older adults aged over 85 gift a quality to urban living that is neighbourliness. Amidst the busyness of urban life, they are going about their everyday being neighbourly. Everyday neighbourhood participation is the spirt of neighbourliness.
Keywords: Participation; Urban; Neighbourhood; Older adults; Hermeneutic phenomenology; Age-friendly; Ontology